Pengaruh Deskripsi Pekerjaan terhadap Kinerja Pegawai Negeri Sipil pada Kantor Camat Tembilahan - Meilisa Syelviani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
Job description or work flows is an important thing that needed in every company or organization. The purpose of this study is to determine the effect of job description on civil servants performance in Tembilahan subdistrict office .Independent variable of this research is job description, and dependent variable is performance. Population of this research are 30 Civil Servants workers in Tembilahan subdistrict office.Sampling technique used is total sampling or census. Data analysis used is linear regression. Theresult showed that there is significance influence between job description against civil servants performance in Tembilahan Subdistrict office with the number of adjusted R square 72 percent, means the other 28 percent of employees performance influences by another factors. Keywords: Job Descriptions, Performance